Exploring Student Misconceptions about Concurrency Using Sonic Pi - Delzanno, Giorgio; Guerrini, Giovanna; Traversaro, Daniele (Proceedings - Euromicro Workshop on Parallel and Distributed Processing, 2025)
As the importance of concurrent and multithreaded programming continues to grow, many universities have incorporated these concepts into their introductory courses. Sonic Pi, a programming language designed for music creation, provides valuable support for exploring concurrency due to its simplified multithreading abstractions and its domain-specific nature. In this paper, we outline several teaching experiments aimed at undergraduate computer science students, using an interdisciplinary pedagogical approach that introduces concurrency early using Sonic Pi. The activities consist of code comprehension and code composition tasks in a collaborative learning environment. Our primary research goal is to explore and discuss students' misconceptions about concurrency, and then draw some preliminary considerations and connections to analogous misconceptions in traditional concurrent programming languages.